WRN inhibits oxidative stress-induced apoptosis of human lensepithelial cells through ATM/p53 signaling pathway and its expression is downregulated by DNA methylation - Shengqun Jiang; Jiansu Chen (BMC, 2020)
Abstract Background Apoptosis and oxidative stress are the main etiology of age related cataract (ARC). This article aims to investigate the role of WRN in lens epithelial cells (LECs). Methods We estimated the methylation level of WRN in anterior lens capsule tissues of ARC patients. SRA01/04 (LECs) cells were treated with H2O2 or combined with 5-aza-2-deoxycytidine (5-Aza-CdR) or chloroquine. CCK8 and flow cytometry were performed to explore proliferation and apoptosis. The content of ROS was detected by fluorescent probe DCFH-DA. The gene and protein expression was assessed by quantitative real-time PCR or western blot. Results WRN was down-regulated and the methylation level of WRN was increased in the anterior lens capsule tissues. WRN overexpression and 5-Aza-CdR enhanced proliferation and repressed apoptosis and oxidative stress of SRA01/04 cells. 5-Aza-CdR enhanced WRN expression. WRN knockdown inhibited proliferation and promoted apoptosis and oxidative stress of SRA01/04 cells, which was rescued by 5-Aza-CdR. WRN overexpression and 5-Aza-CdR repressed ATM/p53 signaling pathway. Furthermore, chloroquine inhibited proliferation and promoted apoptosis and oxidative stress of SRA01/04 cells by activating ATM/p53 signaling pathway. The influence conferred by chloroquine was abolished by WRN overexpression. Conclusion Our study reveals that DNA methylation mediated WRN inhibits apoptosis and oxidative stress of human LECs through ATM/p53 signaling pathway.